Miguel S. Wionczek. El nacionalismo mexicano y la inversión extranjera. México : Siglo XXI Editores, 1967. 314 p. - Silva Herzog, Jesús (Estudios Demográficos y Urbanos, 1969)
MIGUEL S. WIQNCZEK, El nacionalismo mexicano y la inversión extranjera. México, Siglo XXI Editores, 1967.